146k views
1 vote
16-19!!! NEED NOW!!!

16-19!!! NEED NOW!!!-example-1
User Robmzd
by
6.3k points

2 Answers

4 votes

Answer:

(15 solutions)


2x + 9 = y \\ - 4x - 3 = y \\ so \: both \: equation \: is \: equal \\ 2x + 9 = - 4x - 3 \\ 2x + 4x = - 3 - 9 \\ 6x = - 12 \\ x = ( - 12)/(6) \\ x = - 2

if this solution is correct then I'll solve another..... please reply my solution is correct or wrong

User Will Dean
by
7.1k points
2 votes
-3 explanation:hope it helps
User GeekyMonkey
by
5.9k points